Cateterismo venoso central y perforación de miocardio. Presentación de un caso. - ORMEA VILLAVICENCIO, Antonio; LEYVA HURTADO, Francisco (Revista Médica Herediana, 2013)
The use of central venous catheters has a wide use in our hospitals, but it is not exempt from complications. We report a 18 years old woman who had one of this life involved complication. The patient died and necropsy she was diagnosed as follow: perforation of miocardium and pericardial tamponade. The possible mechanism of perforation it was a gradual form which has several causes. It is very important to understand the different forms of perforation and also to evaluate frequently every central venous catheter to prevent all these fatal ocurrences.